Conservation Species of NTFPs Through Agroforestry for Community Livelihoods in Sikka, East Nusa Tenggara - Njurumana, Gerson N; Dona Octavia (Journal of Sylva Indonesiana, 2020)
Conservation and development of non-timber forest product (NTFPs) commodities in East Nusa Tenggara (NTT) are urgently needed. NTFPs are a source of livelihood for the rural communities around the forest areas. NTFPs development around the forest areas is needed as a means to create livelihoods and reduce poverty. The management strategy for forest areas based on integrating conservation and community welfare improvement is needed. The research aims to determine the NTFPs potency in Sikka Regency and the socio-economic conditions of NTFP farmers and to initiate the conservation and development of NTFPs based on the agroforestry approach. The research was conducted through literature review, secondary and primary data collection through surveys, interviews and field observations. The results of the study showed that tamarind (Tamarindus indica L.), candlenut (Aleurites moluccana (L) Willd.), areca nut (Areca cathecu L.), and betel (Piper betle L.) is the major of NTFP commodities in Sikka district. The socio-economic conditions of NTFP farmers on surrounding farmer are not prosperous yet, and highly depend on the sustainability of NTFP production. Community initiatives to conserve and regenerate NTFPs through agroforestry need to be improved, especially in improving the rate of plant growth. Technical assistance to increase community capacity in conservation and development of NTFPs around forest areas and private land is still needed.